(3eONd Edi GdGPGYGJ GdeMdjI aj GdYGde h bVGjG GdeLJeY (B/s - (3GSYjOGfj, SdGejs; (3SYjOs ((3GdLRGFQ (B:s (3OGQ GdNdOhfjI ,s, 2016)
(3JeKd GdJfejI GMO GdYhGed h GdOhGaY GdCSGSjI dEfTGA GdGPGYGJ GdeMdjI ef GLd JaYjd GdeTGQcI aj GdJfejI (B,(3MjK Gf GdOhd GdfGejI dGJSJWjY Gf JMbb CgOGa GdJfejI Ohf Gf Jhdj GgJeGeG HCaQGOgG aj eLJeYGJge GdeMdjI hbO COQcJ Ohd YOjOI Gf GaVd CSGdjH GdGYdGe dJMbjb eTGQcI aYGdI ef LGfH GdLeGgjQ aj NWWh HQGeL GdJfejI gh GdhUhd Edi gPg GdLeGgjQ aj HjFGJge GdeMdjI (B,(3aCfTCJ YOjOG ef hSGFd GdGYdGe GdeMdjI cGdUMa h GdeLdGJ h GdGPGYGJ h GdbfhGJ GdJdjaRjhfjI GdeMdjI h gcPG CUHM gPG GdfeW ef GdGPGYGJ VQhQI dcGaI GdOhd GdeJbOeI h GdfGejI h ef GdeYQha Gf GdCaQGO dG jecf Gf jfSdNhG Yf HjFJge GdeMdjI MjK jROGO GdGQJHGW HGdGYdGe GdeMdj GdOGNdj HeG jJab eY NUhUjI GdecGf h GdTYhH h GdKbGaGJ (B.s
Keywords: (3GdEPGYI GdeMdjIs; (3Yde GdELJeGYs